Pulling the Heartstrings: Employer Branding, Engagement, and the Retention of Millennial Talent in Higher Education - Della Edelweiss Manalu; Yohana F. Cahya Palupi Meilani (Feedforward: Journal of Human Resource, 2025)
In a progressively competitive global environment, employer branding has emerged as a vital element in talent retention, especially among millennials who constitute a significant portion of the workforce. Higher education institutions contribute to knowledge advancement and the establishment of an appealing work environment for their personnel. The elevated turnover rate among millennials presents a difficulty for businesses, especially institutions. This study seeks to examine the influence of corporate branding on talent retention, utilizing employee engagement and affective commitment as mediating variables. The study used a quantitative methodology including a sample of 50 permanent staff members at XYZ University. The employed sample method is purposive sample, with data gathered using a questionnaire. Data were examined utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that employer branding positively influences employee engagement and affective commitment. Employee engagement substantially affects talent retention, although affective commitment does not directly influence it. Furthermore, employee engagement is established as a crucial mediator in the correlation between company branding and talent retention, although affective commitment does not function as a significant mediating variable. This study underscores that effective employer branding must prioritize the enhancement of employee engagement to bolster talent retention within higher education institutions. Organizations are encouraged to cultivate an inclusive workplace, implement supporting policies, and provide career development opportunities to enhance employee engagement and loyalty.